2012
DOI: 10.3109/07357907.2012.691193
|View full text |Cite
|
Sign up to set email alerts
|

Biological Response of Nasopharyngeal Carcinoma to Radiation Therapy: A Pilot Study Using Serial18F-FDG PET/CT Scans

Abstract: We used serial (18)F-fluorodeoxyglucose positron emission tomography/computed tomography ((18)F-FDG PET/CT) to evaluate tumors' maximum standardized uptake value (SUV(max)) before, during, and after radiotherapy to explore the biological behavior of and response to radiation therapy in various subtypes of nasopharyngeal carcinoma (NPC). Sixty-one patients with pathologically diagnosed NPC were prospectively enrolled into the study. WHO type II(B) disease had a higher initial SUV(max) and more significant biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Current studies have confirmed that 18 F-FDG PET/CT is superior to CT and MRI in distinguishing tumor and fibrosis with the ability to reveal tissue metabolism. However, the local inflammation also shows tracer uptake for a period after radiotherapy, which means assessment immediately after the completion of radiotherapy is extremely difficult (42). In general, 18 F-FDG PET/CT is routinely performed 3 months after radiotherapy which is often recommended in clinical practice but unavoidably delays the treatment assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have confirmed that 18 F-FDG PET/CT is superior to CT and MRI in distinguishing tumor and fibrosis with the ability to reveal tissue metabolism. However, the local inflammation also shows tracer uptake for a period after radiotherapy, which means assessment immediately after the completion of radiotherapy is extremely difficult (42). In general, 18 F-FDG PET/CT is routinely performed 3 months after radiotherapy which is often recommended in clinical practice but unavoidably delays the treatment assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment details of Chinese patients have been published previously [ 15 ]. Most patients received IMRT with a total tumor dose of 66–78 Gy in 31 to 39 fractions.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed PET images and patient data from Xiamen, China and CharitĂ© Berlin, Germany plus additional images and patient data from three American databases, available in the cancer imaging archive [11][12][13][14]. Data for the Chinese patients and the patients of the cancer imaging archive have been published previously [15][16][17][18].…”
Section: Patientsmentioning
confidence: 99%
“…Positron emission tomography-computed tomography (PET-CT) using 18 F-fluoro-2-deoxy-D-glucose (FDG), namely, FDG PET-CT, provides combined anatomic and metabolic information in one examination. Studies have shown that PET-CT has the potential value in the early treatment and posttreatment assessment by improving the differentiation between residual/recurrent disease and postchemoradiation fibrosis [ 1 , 2 ] and may serve as prognostic indicators especially in patients with locoregionally advanced disease [ 3 ]. Standardized uptake value (SUV) and the metabolic tumor volume have been demonstrated to be useful for prognostication in NPC patients in some studies but these findings have not been consistent [ 4 – 9 ].…”
Section: Introductionmentioning
confidence: 99%